The Effect of Compensation, Workplace Environment, and Organizational Commitment on Non-Government Health Care Practioner’s Performance - Susanti Angraeni; Rokiah Kusumapadja; Rian Adi Pamungkas (Journal of Multidisciplinary Academic, 2020)
Compensation can improve work performance, motivate employees and bring job satisfaction. This study aimed to determine the effect of compensation, workplace environment, and organizational commitment on work performance. The sample used was non civil servant health workers at X Hospital South Tangerang with a total of 108 correspondent who has work period of more than 3 years. In this research design we use a quantitative study with a cross sectional approach. Furthermore, the Interviews, Key Performance Indicator data collection, and questionnaires were used as methods of collecting data. Here, the data analysis technique in this study was performed using multiple linear regression with the SPSS 25 program. The results showed the compensation, workplace environment, and organizational commitment simultaneously and partially had a positive and significant effect on non- Government Health Care Practioner’s Performance at X Hospital in South Tangerang with contributed 67.6% to the performance. Based on the results, the regression analysis, with coefficient value was obtained which indicated that the compensation regression coefficient (0.379) had the highest value compared to the regression coefficient value for workplace environment (0.259) and organizational commitment (0.254). These results indicated that compensation is the more dominant factor affecting the performance of non-Government Health Care Practioner’s Performance on X Hospital, South Tangerang, compared to workplace environment and organizational commitment.